USING VISUAL ANALYSIS AND COLOUR ANALYSIS TECHNIQUES TO ENHANCE STUDENT CREATIVITY: A STUDY ON HOW COLOUR AND VISUAL ANALYSIS TECHNIQUES CAN BE APPLIED TO ENHANCE STUDENTS' CREATIVE EXPRESSION - Karar Jamhour Mehdi Karmsh (Scholars Digest Publishing, 2024)
The study aimed to determine the extent to which the use of visual analysis and color analysis techniques affects students' creative expression. It also aimed to measure the differences between the experimental group and the control group in creative expression after applying the training program, and to explore the relationship between visual and color analysis skills and the various dimensions of creativity such as originality, flexibility, fluency, and expansion. In addition to providing recommendations on how to integrate visual analysis and color analysis techniques into educational curricula to enhance creativity. The study relied on an experimental methodology that included an experimental group and a control group, where the experimental group was trained on visual analysis skills and color analysis techniques. The study used a test to measure creative expression as the main tool, and it was applied to a sample of 40 tenth-grade female high school students, with an average age of 179.6 months. The results showed that there were statistically significant differences between the two groups in favor of the experimental group in all dimensions of creativity (originality, flexibility, fluency, expansion, and total score). Based on the results, the study recommends implementing training programs based on visual analysis and color analysis techniques in school curricula to enhance students’ creativity skills, and integrating visual arts further into education to stimulate critical and creative thinking.
Keywords: visual analysis, color analysis techniques, creativity, creative expression.